Development of Website-Based Learning Media in Grammatics Course A1 - Indah Surya Cerah Marpaung; Pujiastuti, Suci (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to find out the difficulties faced by class C 2023 students of the German Language Study Program, State University of Medan, in learning Germany using web-based learning media for the A1 Grammar course. This paper is a literature study that uses a quantitative descriptive method with the theory of Richey and Klein 2009. The data of this research is in the form of material taken from the book